Adsorption of primary substituted hydrocarbons onto solid gallium substrates - De Silva, Chrishani Maheshwari (Kansas State University, 2013)
Adsorption of a series of primarily substituted hydrocarbons (RX; C[subscript]18H[subscript]37PO(OH)[subscript]2 (ODPA), C[subscript]17H[subscript]35COOH, C[subscript]18H[subscript]37OH, C[subscript]18H[subscript]37NH[subscript]2 and C[subscript]18H[subscript]37SH) onto solid gallium substrates with and without UV/ozone treatment was studied using contact angle goniometry, spectroscopic ellipsometry and cyclic voltammetry (CV). UV/ozone treatment offered a hydrophilic surface (water contact angle ([theta][superscript]water) less than 10°), reflecting the formation of a surface oxide layer with the maximum thickness of ca. 1 nm and possibly the removal of surface contaminants. Upon immersion in a toluene solution of a RX, [theta][superscript]water increased due to adsorption of the RX onto gallium substrates. In particular, UV/ozone-treated gallium substrates (UV-Ga) immersed in an ODPA solution exhibited [theta][superscript]water close to 105°. The ellipsometric thickness of the adsorbed ODPA layer was ca. 2.4 nm and CV data measured in an acetonitrile solution showed significant inhibition of redox reaction on the substrate surface. These results indicate the formation of a densely-packed ODPA monolayer on UV-Ga. The coverage of a C[subscript]17H[subscript]35COOH layer adsorbed onto UV-Ga was lower, as shown by smaller [theta][superscript]water (ca. 99°), smaller ellipsometric thickness (ca. 1.3 nm) and smaller electrode reaction inhibition. Adsorption of the other RX onto UV-Ga was weaker, as indicated by smaller [theta][superscript]water (82-92°). ODPA did not strongly adsorb onto UV-untreated gallium substrates, suggesting that the ODPA adsorption mainly originates from hydrogen bond interaction of a phosphonate group with surface oxide. These results will provide a means for controlling the surface properties of oxide-coated gallium that play an essential role in monolayer conductivity measurements and electroanalytical applications.
Keywords: Adsorption; Primary substituted; Octadecylphosphonic acid; Gallium; Chemistry (0485)